Characterization of rat and mouse acidic milk oligosaccharides based on hydrophilic interaction chromatography coupled with electrospray tandem mass spectrometry. (1st May 2021) - Li, Jiaqi; Jiang, Maorong; Zhou, JiaoRui; Ding, Junjie; Guo, Zhimou; Li, Ming; Ding, Fei; Chai, Wengang; Yan, Jingyu; Liang, Xinmiao
Graphical abstract: Highlights: Acidic milk oligosaccharides in rats and mice were analysed using LC-CID-MS/MS. 15 acidic oligosaccharides were identified in rat milk and 14 in mouse milk. 6- O -sulphation at the reducing-side galactose was found in 4 of the oligosaccharides. Abstract: Oligosaccharides are one of the most important components in mammalian milk. Milk oligosaccharides can promote colonization of gut microbiota and protect newborns from infections. The diversity and structures of MOs differ among mammalian species. MOs in human and farm animals have been well-documented. However, the knowledge on MOs in rat and mouse have been very limited even though they are the most-widely used models for studies of human physiology and disease. Herein, we use a high-sensitivity online solid-phase extraction and HILIC coupled with electrospray tandem mass spectrometry to analyze the acidic MOs in rat and mouse. Among the fifteen MOs identified, twelve were reported for the first time in rat and mouse together with two novel sulphated oligosaccharides. The complete list of acidic oligosaccharides present in rat and mouse milk is the baseline information of these animals and should contribute to biological/biomedical studies using rats and mice as models.